Microscopic models of hardness - Gao, F.M.; Gao, L.H. (Сверхтвердые материалы, 2010)
Recent developments in the field of microscopic hardness models have been reviewed. In these models, the theoretical hardness is described as a function of the bond density and bond strength. The bond strength may be characterized by energy gap, reference potential, electron-holding energy or Gibbs free energy, and different expressions of bond strength may lead to different hardness models. In particular, the hardness model based on the chemical bond theory of complex crystals has been introduced in detail. The examples of the hardness calculations of typical crystals, such as spinel Si₃N₄, stishovite SiO₂, B₁₂O₂, ReB₂, OsB₂, RuB₂, and PtN₂, are presented. These microscopic models of hardness would play an important role in search for new hard materials. Зроблено огляд останніх розробок в області мікромоделей твердості. У цих моделях теоретичну твердість описано як функцію щільності та міцності зв’язку. Міцність зв’язку може бути охарактеризована шириною забороненої зони, опорним потенціалом, енергією утримання електрона або вільною енергією Гіббса. Тому різні вирази міцності зв’язку приведуть до різних моделей міцності. Зокрема, докладно описано модель твердості, основану на теорії хімічного зв’язку складних кристалів. Наведено приклади розрахунків твердості типових кристалів, таких як шпінель Si₃N₄, стишовіт SiO₂, B₁₂O₂, ReB₂, OsB₂, RuB₂ и PtN₂. Ці мікромоделі твердості будуть грати важливу роль в пошуку нових твердих матеріалів. Дан обзор последних разработок в области микромоделей твердости. В этих моделях теоретическая твердость описана как функция плотности и прочности связи. Прочность связи может быть охарактеризована шириной запрещенной зоны, опорным потенциалом, энергией удержания электрона или свободной энергией Гиббса. Поэтому различные выражения прочности связи приведут к различным моделям твердости. В частности, подробно описана модель твердости, основанная на теории химической связи сложных кристаллов. Привены примеры расчета твердости типичных кристаллов, таких как шпинель Si₃N₄, стишовит SiO₂, B₁₂O₂, ReB₂, OsB₂, RuB₂ и PtN₂. Эти микромодели твердости будут играть важную роль в поиске новых твердых материалов.